1998
DOI: 10.1165/ajrcmb.19.4.2870
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Apoptosis of Dendritic Cells in the Rat Tracheal Mucosa

Abstract: Dendritic cells are antigen-presenting cells that constitutively express high levels of major histocompatibility complex class II (Ia) antigen on their plasma membrane. Previous studies have shown that the number of dendritic cells in the rat airway mucosa decreases rapidly after glucocorticoid treatment. We sought to determine whether apoptosis contributes to this steroid-induced cell decrease. Dendritic cells in tracheal whole mounts were revealed by immunoperoxidase staining using the OX-6 (anti-Ia) monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…8). This may represent a potential mechanism for rapid local tissue memory T cell activation by pathogen-derived peptides released by local phagocytes, which our group and others have shown to be recruited into the airway mucosa during acute inflammatory responses (30), while restricting naive T cell activation to whole protein Ags to DLNs.…”
Section: Discussionmentioning
confidence: 85%
“…8). This may represent a potential mechanism for rapid local tissue memory T cell activation by pathogen-derived peptides released by local phagocytes, which our group and others have shown to be recruited into the airway mucosa during acute inflammatory responses (30), while restricting naive T cell activation to whole protein Ags to DLNs.…”
Section: Discussionmentioning
confidence: 85%
“…Besides the previously reported negative effects on DC trafficking (34), function (25,30) and increases in apoptosis of DC (35), glucocorticoids also have shown in many studies variable`suppressive' and`altering' effects on the maturation of DC. This probably depends on the dose and time schedule of exposure, and the maturation state of the target DC population.…”
Section: Discussionmentioning
confidence: 96%
“…These data are in agreement with previous studies that showed that glucocorticoid can induce the apoptosis of DCs. 21 The sequential responses were uniquely found in survivors but not in NS patients because mDC recovery occurred drastically and almost simultaneously with improved liver function. Although our data suggest that a strong mDC recovery may be an important factor for favorable responses to MP treatment, it was rational to speculate that the rebound of circulating mDC numbers may not simply be a direction result of the redistribution of mDCs from the liver, where they function as effectors of ACLF pathogenesis, to the blood.…”
Section: Discussionmentioning
confidence: 99%